Dynamical behaviour of ultrathin [CoFeB (t CoFeB )/Pd] films with perpendicular magnetic anisotropy - Ana S. Silva (Nature Portfolio, 2021)
Abstract CoFeB-based ultrathin films with perpendicular magnetic anisotropy are promising for different emerging technological applications such as nonvolatile memories with low power consumption and high-speed performance. In this work, the dynamical properties of [CoFeB (t CoFeB )/Pd (10 Å)]5 multilayered ultrathin films (1 Å ≤ t CoFeB  ≤ 5 Å) are studied by using two complementary methods: time-resolved magneto-optical Kerr effect and broadband ferromagnetic resonance. The perpendicular magnetization is confirmed for multilayers with t CoFeB  ≤ 4 Å. The effective perpendicular magnetic anisotropy reaches a clear maximum at t CoFeB  = 3 Å. Further increase of CoFeB layer thickness reduces the perpendicular magnetic anisotropy and the magnetization became in-plane oriented for t CoFeB  ≥ 5 Å. This behaviour is explained by considering competing contributions from surface and magnetoelastic anisotropies. It was also found that the effective damping parameter α eff decreases with CoFeB layer thickness and for t CoFeB  = 4 Å reaches a value of ~ 0.019 that is suitable for microwave applications.